Textile industry consulting report case of CREDITEX S.A.A. - Ramos Alvarado, Janine Estela (2020)
CREDITEX S.A.A. is a company dedicated to the manufacture and sale of yarns, fabrics and garments made with Pima and Tangüis cotton, to both national and international markets. The company is characterized by being vertically integrated, managing its operations in seven plants distributed along the Peruvian coast, thus achieving absolute control during the entire manufacturing process. CREDITEX belongs to the economic group Corporación Cervesur S.A.A., and employs around 1500 people, including operators and administrative staff, as well as a board of Executive Directors composed by six people. In the last five years, the company has shown a decline in sales, which has been notably reflected in the financial statements, for instance, an EBITDA of PEN 12'370 miles was reached in 2018 and PEN 9'171 miles in 2019, indicating a decline of around 25%. This is mainly due to the increase in production costs and it has been possible to demonstrate during the analysis carried out in the present thesis that the costs of materials and labor have had a significant influence on this rise. Hence, the international demand has been reduced as customers have opted for other more economical options. Under this scenario and the prompt need to solve the reduction in sales, it is proposed the strategy of product development for an existing market, which refers to the United States; with a focus on the category of sportswear targeting the premium segment, in addition to the implementation of the FairTrade or Made in Green seal in order to have an added value on the current products and justify their prices. Finally, it is proposed specific recommendations for CREDITEX to improve its internal processes and, consequently, sales and positioning in the local and international markets.